Mass spectrometric investigations of the action of hypochlorous acid on monomeric and oligomeric components of glycosaminoglycans - Jenny Leopold; Patricia Prabutzki; Ariane Nimptsch; Jürgen Schiller (Biochemistry and Biophysics Reports, 2023)
Hypochlorous acid (HOCl) is a strong non-radical oxidant, which is generated during inflammatory processes under the catalysis of the enzyme myeloperoxidase (MPO). HOCl reacts particularly with sulfhydryl and amino acid residues but affects also many other biomolecules. For instance, the glycosaminoglycans of articular cartilage and synovial fluids (such as hyaluronan) undergo degradation in the presence of HOCl at which the native polysaccharide is fragmented into oligosaccharides in a complex reaction.This is an initial mass spectrometry (MS)-based investigation dealing with the HOCl-induced degradation of glycosaminoglycans and the conversion of the related monosaccharides into chlorinated products. In particular, it will be shown that the reaction between HOCl and hyaluronan is slower than originally assumed and results in the generation of different products (particularly the hyaluronan monosaccharides) by the cleavage of the β-1,3/1,4-glycosidic linkages. The MS detection of chlorinated products is, however, only possible in the case of the monosaccharides. Potential reasons will be discussed.